Drivers of plant-associated invertebrate community structure in West-European coastal dunes - Ruben Van De Walle; Maxime Dahirel; Ward Langeraert; Dries Benoit; Pieter Vantieghem; Martijn L. Vandegehuchte; François Massol; Dries Bonte (npj Biodiversity)
Abstract The organisation of species assemblages is affected by environmental factors acting at different spatial scales. To understand the drivers behind the community structure of invertebrates associated with marram grass -a dune-building ecosystem engineer -, we set up a stratified sampling scheme in six biogeographic sectors along the North Sea. We tested to which degree invertebrate species composition is affected by the spatial organisation of marram grass tussocks. Using distance-based RDA and a joint species distribution modelling approach, we show biogeography to be the most important driver, followed by species-specific responses to marram grass cover and vitality. Traits and phylogeny had a minor influence on the species distribution patterns. The residual species covariation suggests negative interactions between groups of specialist and generalist species. Our research indicates that the biological value of nature-based solutions for coastal protection can be optimized by the design of a heterogeneous marram grass planting scheme and/or development.